The meaning of radicalisation in modern social pedagogy - Ana Bogdan Zupančič (University of Maribor Press, 2021)
The article defines radicalisation as part of the processes of modern liberation, which are recognised in the interlacement of emancipatory potential in social pedagogy and mobilisation in the theory of community development. In parallel to this, we problematise the internally divided socio-pedagogical attitude, which, on the one hand, seeks to liberate, and on the other hand, is repeatedly caught in the preservation of existing "oppressive" power relations. In doing so, we consider the concerns regarding political action as the goal of "radicalising" social pedagogy, which indicate that in social pedagogy we have internalized collaboration as a democratic "norm" of solving social and other societal issues and thus accepted it as the only formally realistic option to achieve structural change.